Exploring Experience: Teacher Narratives and Narratives of Teaching - Trudy Ambler; Puspha Sinnayah; Joanna Lim (Education Sciences)
In this Special Issue (SI), we have published recent scholarship addressing (a) narrative ways of knowing, (b) the diversity of methods used for researching experience and (c) issues related to the use of narrative to explore the experiences of individuals within an educational context [...]